Phosphorus Removal Rates from Sod Production Systems - Maria L. Silveira; Randy Bateman; Joseph Walter; Jerry Sartain; Christa L. Kirby; Pete Deal (EDIS)
SL309, a 6-page illustrated report by Maria L. Silveira, Randy Bateman, Joseph Walter, Jerry Sartain, Christa L. Kirby, and Pete Deal, presents the results of a study to evaluate P removal rates in different sod production systems in central and south Florida. Includes references. Published by the UF Department of Soil and Water Sciences, November 2009.